Patient satisfaction while enrolled in clinical trials: A literature review - Ilufredo Tantoy; Andrea Bright; Evan Paelmo; Emily Moreland; Ashley Trost; Joan Pasquesi; Charlotta Weaver; Richard D'Aquila (The Beryl Institute, 2021)
Patient satisfaction surveys may not adequately reflect organizations that conduct research in patients who enroll in clinical trials. The purpose of this systematic literature review was to summarize the current state of knowledge of patient satisfaction while enrolled in clinical trials utilizing a widely used, validated patient satisfaction instrument. A comprehensive literature search was conducted using CINAHL, EMBASE, PsycInfo, PubMed and Web of Science. Studies were evaluated in terms of clinical trial participation; assessment conducted during or after participation; utilization of a validated instrument; a pharmacological intervention; and the paper was published in English. Only nine studies met this review's inclusion criteria. Eight studies utilized investigator-developed patient satisfaction instruments and only one study used a widely-used, validated patient satisfaction instrument. Two studies evaluated patient satisfaction during the development of the instrument. Of the nine studies identified, only five patient satisfaction domains were common across the studies and only study evaluated the associations of patient satisfaction responses with clinical outcomes. Given the importance of patient satisfaction surveys, future studies need to focus on this subset of patients enrolled in clinical trials to evaluate a patient's experience and its impact on protocol compliance and protocol outcomes. Future studies need to focus on domains associated with clinical trial participation and look beyond the current patients' general expectations about healthcare accessibility, facilities, healthcare team clinical skills, and their ability to focus and listen to the patients' concerns. Experience Framework This article is associated with the Policy & Measurement lens of The Beryl Institute Experience Framework. (https://www.theberylinstitute.org/ExperienceFramework). <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Policy%20%26%20Measurement%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.